Study on the Properties of Polyurethane–Urea Elastomers Prepared by TDI/MDI Mixture - Xiangcheng Bian; Jiaguo He; Maoyong He; Bingxiao Liu; Yinzhu Zhang (International Journal of Polymer Science)
As well known, the easily volatile 2,4-toluene diisocyanate (TDI) monomer poses a great threat to the environment and human health during the preparation of polyurethane–urea elastomer (PUU). Hence, 4,4′-diphenylmethane diisocyanate (MDI), an isocyanate with significantly lower toxicity compared to TDI, was used as a partial substitute for TDI to prepare PUU through the prepolymerization method with other raw materials including polytetramethylene glycol (PTMG) and 4,4′-methylene-bis(2-chloroaniline) (MOCA) in this paper. The effect of the molar ratio of TDI to MDI on the pot life, light transmittance, mechanical properties, thermal stability, and dynamic mechanical properties of PUU was investigated. The results show that the pot life of PUU decreases with the MDI content increasing; however, the density of PUU increases. Besides, the tensile strength and the transparency of PUU exhibit a trend of first rising and then falling as the MDI content increases. Particularly, pot life, light transmittance, tensile strength, permanent set, and initial decomposition temperature of PUU with a molar ratio of TDI to MDI set at 7/3 are 522 s, 90.0% at 550 nm, 52.9 MPa, 9.8%, and 287.8°C, respectively. This is to say, the PUU prepared in our research not only have excellent comprehensive performance but also greatly eliminate the harm caused by TDI volatilization, which can be applied in areas requiring high transparency.